Herodium as a Reflection of Herod's Policy in Judea and Idumea - Bourgel, Jonathan (Zeitschrift des Deutschen Palästina-Vereins, 2019)
Based on Josephus' writings, it is commonly agreed that Herod the Great (37-4 B.C.E.) started building Herodium around 24-23 B.C.E. on the site where he defeated Mattathias Antigonus' supporters in 40 B.C.E. While there is no reason to doubt that Herodium was erected as a memorial to this battle, it is noteworthy that it also served as a fortress, a palace complex and the capital of a toparchy (basic administrative district). It therefore is obvious that apart Herod's desire to perpetuate the memory of his victory over Antigonus' supporters, there were other considerations behind his decision to build Herodium. Furthermore, recent archaeological excavations have revealed that Herodium was founded earlier than 24-23 B.C.E., probably in the 30s B.C.E., and that it underwent several construction phases up to Herod's death. This paper proposes a partially refined chronology for Herodium and aims to discern the historical circumstances behind each of its building phases. It is based on the analysis of textual evidence combined with updated archaeological information and geographical data. It argues that Herodium's location on the traditional boundary between Judea and Idumea largely determined its establishment and development.